PENGARUH MEDIA AUDIOVISUAL DAN GERAK KINESTETIK TERHADAP KEMAMPUAN MEMBACA KELAS I SDN 55 PALEMBANG - Olipia, Salma; Wahidy, Achmad; El Cintami Lanos, Mushana (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This research is motivated by the low initial reading ability of students and the lack of varied learning methods involving visual, auditory, and motor activities. Learning tends to be teacher-centered, resulting in a lack of student engagement and low interest in reading. The purpose of this study was to determine the effect of Audiovisual Media and Kinesthetic Movement on the reading ability of grade 1 SDN 55 Palembang. This study used a Quasi-Experimental method with a quantitative approach using a Pretest-Posttest Control Group Design. The results of this study were supported by the results of the hypothesis test, which obtained a sig (2-tailed) of 0.000 <0.05, indicating a significant effect of Audiovisual Media and Kinesthetic Movement on reading ability. The average posttest score for the control class was 78.52, while the average posttest score for the experimental class was 93.52. This indicates that the experimental class achieved better reading skills than the control class after receiving the treatment. Therefore, audiovisual media and kinesthetic movement influenced the reading skills of first-grade students